Optimization and characterization of bioactive secondary metabolites from Streptomyces sp CMSTAAHL-4 isolated from mangrove sediment - Selvaraj Jeraldin Nisha; Ganapathi Uma; Ramamoorthy Sathishkumar; Vincent Samuel Gnana Prakash; Rimal Isaac; Thavasimuthu Citarasu (BMC Microbiology)
Abstract Background Ten morphologically different actinomycetes were isolated from mangrove sediments of Manakudy, Kanyakumari District, India. The potent strain was selected based on their primary screening against Gram positive Staphylococcus aureus, Enterococcus faecalis and Gram negative Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Salmonella typhi bacterial pathogens. The selected strain was identified as Streptomyces sp CMSTAAHL-4 by 16S rRNA sequencing. The media optimization for secondary metabolites production was performed by One-Variable at a Time and Response Surface Methodology-Central Composite Design. Minimum inhibitory concentration and minimum bacterial concentration for the extracted secondary metabolites were determined. The antioxidant potential of the secondary metabolites showed that the concentration of the metabolites increases, with the percentage of inhibition. The anti-inflammatory activity of the secondary metabolites found that maximum activity was observed at 500 µg/ml of the metabolites. Alcohols, alkenes, alkynes, alkyl halides, carboxylic acids, aliphatic esters functional groups were identified by fourier transform infrared spectroscopy, gas chromatography and mass spectrometer analysis of the secondary metabolites revealed five bioactive compounds. The X-ray diffraction analysis revealed that the secondary metabolites are amorphous. The thermogravimetric analysis showed the thermal stability of secondary metabolites. Atomic force microscopy analysis revealed specific structural characteristics of the secondary metabolites, which may be associated with their potential biological activities. Conclusions The results showed that the antibacterial, antioxidant, and anti-inflammatory chemicals present in the isolated secondary metabolites give them therapeutic properties.